A vulture that does not eat carrion: reflections on the character and our social realities. (The Voz a Vos Bulletin, 2024)
The presentation explores the symbol of the vulture in the play Reino de Carroñeros as a representation of social and political disenchantment. Through the voices of Kelly Rojas, from seventh grade, and Salomé Cárdenas, from fourth grade, members of the ALCATOE theatre group from the Álvaro Camargo de la Torre ETB School, it examines how this character, tired of feeding on carrion, symbolizes the frustration of those who want a real change in their lives, instead of settling for the crumbs offered by the rulers. The analysis of the dramatic text reveals how the characteristics of the vulture reflect the struggle for dignity and the right to aspire to more, challenging the dynamics of power and claiming a space for hope and social action.The presentation also invites us to reflect on social expectations and the role that the characters play in the construction of collective reality. The importance of not resigning ourselves to the established order and of seeking new possibilities is underlined. In addition, the workshop discusses how theatre can function as a powerful vehicle for social criticism, promoting dialogue and awareness in the community.
Keywords: Social criticism; Social disenchantment; Fight for dignity